Cadmium exposure via food crops: a case study of intensive farming area - Munisamy, Raagheni; Syed Ismail, Sharifah Norkhadijah; Praveena, Sarva Mangala (Science Publications, 2013)
Cadmium (Cd) is ubiquitous in environment and may enter food chain through intense application of phosphate fertilizers to agricultural crops. A cross-sectional study was conducted at Kuala Terla and Blue Valley farming villages, Cameron Highlands to determine cadmium concentration in vegetables and soil and to determine the health risks among respondents. A total of 87 respondents were selected based on inclusive and exclusive criteria. A set of pre-tested questionnaires utilized to obtain socio-demographic information and to predict health risks faced by the respondents based on their vegetable ingestion rate. The Average Daily Dose (ADD) and Target Hazard Quotient (THQ) were determined in this study. Convenient sampling method was employed to obtain 15 paired soil and vegetable samples. Cadmium concentration in the samples was acid digested prior analysis using Flame Atomic Absorption Spectrophotometer (FAAS). The mean ± standard deviation concentrations of Cd in vegetable samples were 0.13±0.082 mg kg-1, within the acceptable range specified by Malaysia Food Regulation 1985 (1 mg kg-1). For sol samples, the mean ± standard deviation concentration of Cd was 2.78±2.83 mg kg-1. Eight out of 11 soil samples exceed the permissible limit of Cd outlined by The Dutch Standard (1 mg kg-1). The findings on THQ demonstrated that all respondents are within the acceptable non-carcinogenic health risk (THQ<1). The results also exhibit that there is no correlation between cadmium in soils and vegetables. There are unlikely potential adverse health impacts arising from Cd through vegetables consumption in this study. Respondents are advised to have a medical check-up in order to determine Cd body burden thus eliminating the risks of acquiring cadmium related diseases.